2006
DOI: 10.1016/j.nuclcard.2006.06.131
|View full text |Cite
|
Sign up to set email alerts
|

Simplified normal limits and automated quantitative assessment for attenuation-corrected myocardial perfusion SPECT

Abstract: Automated detection of CAD by AC and NC MPS demonstrated similar sensitivity, specificity, and normalcy rates. Some gender differences were noted for AC normal limits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 20 publications
0
52
1
Order By: Relevance
“…Separate male and female normal limits were created for standard summed perfusion data from summed short-axis images and for MF MPS data using 16-frame gated MPS data. Normal limits were created for the general population and were not BMImatched; however, we have previously shown that normal limits for high and low BMI groups are not significantly different (3).…”
Section: Patient Population and Acquisition Protocolsmentioning
confidence: 99%
“…Separate male and female normal limits were created for standard summed perfusion data from summed short-axis images and for MF MPS data using 16-frame gated MPS data. Normal limits were created for the general population and were not BMImatched; however, we have previously shown that normal limits for high and low BMI groups are not significantly different (3).…”
Section: Patient Population and Acquisition Protocolsmentioning
confidence: 99%
“…Previously reported PET performance for detection of CAD (sensitivity, specificity, and accuracy) may indeed be different with CT-based systems. The CT misalignment problem may be one of the reasons why in the recent PET/CT study, the data specificity obtained with a PET/CT system (14) was both lower (specificity, 54%) than that previously reported with the PET transmission systems by visual analysis (specificity, 88%) and also slightly lower than that reported for the relative quantification of SPECT with transmission AC (specificity, 80%) for detection of greater than or equal to 70% stenosis (13).…”
Section: Discussionmentioning
confidence: 76%
“…One implication of this finding is that the same normal-limit databases should not be exchanged between these 2 types of AC, because the interstudy variation in normal limits is in the 5%27% range in most segments (13,14). Previously reported PET performance for detection of CAD (sensitivity, specificity, and accuracy) may indeed be different with CT-based systems.…”
Section: Discussionmentioning
confidence: 95%
“…Although some studies reported an increase in the diagnostic accuracy for the detection of coronary artery disease when myocardial perfusion SPECT is attenuation corrected, [21][22][23] only a few investigations addressed the accuracy of attenuation correction without any visual interpretation of corrected and non-corrected data. [24][25][26][27] To avoid any possible bias associated with visual interpretation, in another study Wolak et al 28 evaluated the performance of attenuation correction in 2,624 women by using automated quantitative analysis of myocardial perfusion with QPS. The authors showed no significant diagnostic differences between studies processed with and without attenuation correction.…”
Section: Impact Of Attenuation Correctionmentioning
confidence: 99%